Smart LED high CRI lighting systems. Issue 3 (2nd July 2018) - Grzesiak, Wojciech; Guzdek, Piotr; Maćków, Piotr; Zaraska, Krzysztof; Zbieć, Michal; Jakubowski, Mariusz; Obrębski, Dariusz; Boguszewicz, Piotr; Solnica, Dariusz; Iwanicki, Pawel; Linke, Sebastian; Mahlkow, Adrian
Abstract : Purpose: The purpose of this paper is to present issues related to the design of a modern lighting system based on LED technology. The developed system provides lighting with a high colour rendering index (up to 98); it also has many innovative functions, which make its implementation bring significant energy savings and increase the comfort of work. Design/methodology/approach: In contrast to typical solutions, the dynamic synthesis of white light from six component colours was used in the presented project. This process is controlled by a microcontroller, and there is a colour temperature sensor in the feedback loop. The communication between smart luminaires and sensor modules is provided by means of a ZigBee wireless network. Findings: The correctness of the proposed methodology has been proved by measurements and laboratory tests. Research limitations/implications: The process of improving the lighting system is continued and significant changes in the spectrum of used sensors are expected. Practical implications: The proposed system based on mixing light from six components is an innovative solution that besides undoubted advantages entails a more elaborate electronic circuitry. However, good characteristics of the obtained light, as well as the possibility of compensating for changes in colour temperature of natural light and reducing the impact of aging of LEDs, in the authors' opinion, make the proposed solution find its place on the market. Originality/value: The proposed solution is original, both in terms of the light mixing technique and advanced functionality offered by the system.